Morality stereotyping as a basis of women's in-group favoritism: An implicit approach. (March 2017) - Leach, Colin Wayne; Carraro, Luciana; Garcia, Randi L.; Kang, Jessica J.
Four studies used three different implicit methods (theBrief IAT, Affect Misattribution Procedure, and Lexical Decision Task) to measure women's gender stereotypes of violence, strength, competence, trustworthiness, and sociability. Analyses of response latencies in Study 1 ( N = 100) showed that these stereotypes were based more in in-group favoritism than out-group derogation. Consistent with recent evidence that morality is central to the positive evaluation of in-groups, it was the implicit stereotype of women as more trustworthy that best predicted their implicit in-group favoritism across studies, r (249) = .27. Only by examining such specific stereotype content could we assess the moral stereotype of trustworthiness as distinctly tied to in-group favoritism. Alternative analyses of the two global dimensions of group evaluation (i.e., agency/competence and communion/warmth) obscured differences between the more specific stereotypes. Implications for theory and research on stereotype content, as well as the group favoritism of disadvantaged groups, are discussed.